Accelerated right heart failure due to lung resection in the setting of chronic respiratory failure. Issue 1 (January 2022) - Maaliki, Naji; Verdecia, Jorge; Fasen, Madeline; Ali, Aleem Azal; Aung, Win
Abstract: A 68-year-old woman with a past medical history of chronic obstructive pulmonary disease and squamous cell carcinoma of the lung with recent right upper and middle lobectomy was admitted for dyspnea and volume overload. She was diagnosed with right-sided heart failure (RHF) through clinical, laboratory, and echocardiographic means. In the setting of chronic respiratory failure, the recent right lung lobectomy was deemed to be the inciting factor of the RHF. The mechanism by which RHF occurs in this situation is multifactorial, and it is essential to undergo pre-operative risk stratification and post-operative monitoring to avoid emergent events. <Learning objective: New-onset right heart failure can be a detrimental complication of lung resection surgery in patients with chronic respiratory failure. With proper pre-operative risk stratification and its corresponding post-operative monitoring, we can anticipate such occurrences and avoid emergent admissions, enabling better outcomes in a high-risk patient population.>